(untitled) (Research, Society and Development, 2022)
Serious Mental Disorders affect people all over the world. In Brazil, at least 3% of the population suffers from some type of mental disorder in its most severe form, mainly major depression, in which, in certain cases, drug therapy alone does not have the desired remission effect. In these situations, other therapeutic measures are adopted, such as Electroconvulsive Therapy (ECT), which despite the punitive stigma, has proved to be a great alternative in the treatment of this type of disorder. Thus, this work aims to analyze available evidence on the efficacy and effectiveness of electroconvulsive therapy (ECT) in the treatment of major depression, resistant to psychotropic drugs, but aiming not only for success from the medical point of view, but also from the patient’s point of view. To this end, a systematic and descriptive analysis was carried out using specialized literature on the subject. The results showed that, yes, ECT is effective as a therapy in cases of major depressive disorder, but as long as there is a responsible technical application during treatment, solving patients’ doubts and explaining, that yes, there are side effects, but these are minimal when compared to the benefits of treatment.